2022
DOI: 10.55123/abdikan.v1i2.281
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Psikoedukasi Dampak Cyberbullying Terhadap Kesehatan Mental Pada Siswa

Abstract: Cyberbullying presents a serious challenge to social life that must receive attention in the digital world. This is a frightening event for everyone, especially for teenagers causing depression, low self-esteem, not being able to concentrate in class, declining academic grades, anxiety and even suicide. Seeing the magnitude of the danger caused by the incident, it is necessary to continue to develop efforts to provide awareness to the public, especially social media users, to use it properly and wisely and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Adolescents are going through many changes, including biological, psychological, and social changes. When adolescents have a conflict with their environment, if not handled properly, it can have negative consequences (Kumala & Sukmawati, 2020;Oktariani et al, 2022;Rahayu, 2012). This study found that victims of cyberbullying experience impacts such as stress and anger.…”
Section: Discussion Of the Findingsmentioning
confidence: 82%
“…Adolescents are going through many changes, including biological, psychological, and social changes. When adolescents have a conflict with their environment, if not handled properly, it can have negative consequences (Kumala & Sukmawati, 2020;Oktariani et al, 2022;Rahayu, 2012). This study found that victims of cyberbullying experience impacts such as stress and anger.…”
Section: Discussion Of the Findingsmentioning
confidence: 82%